(untitled) (Journal of Pedagogical Inventions and Practices, 2025)
This article analyzes the issue of improving the methodology of inquiry-based teaching using artificial intelligence (AI). Traditional teaching methods are often insufficient for developing students’ research and independent inquiry skills. Therefore, integrating AI technologies into the educational process has become an essential task. This paper examines the relationship between artificial intelligence and inquiry-based learning (IBL) methodology and explores its application in teaching inorganic chemistry.